AN ANALYSIS OF INDEX, ICON, SYMBOL IN THE SONG OF IKAT AKU DI TULANG BELIKATMU: SAL PRIADI - Kemuning, Maudy Ariana; Sakinah, Myrna Nur (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2020)
This study aims to determine the types of icons, indexes, and symbols contained in the song "Ikat Aku di Tulang Belikatmu" by Sal Priadi. This research can be useful for people because it serves to express the song from the lyrics of the song itself and has the same feeling of the meaning of the song lyrics. The theory used in this study is the sign system theory with a semiotic approach proposed by Charles Sander Peirce. Where this theory can divide the sign system into three parts namely icons, indexes, and symbols. The method used is the Content Analysis method. Content Analysis is research that is a discussion of the contents of written or printed information in mass media and uses the theory of semiotic science in analyzing signs in songs. Thus, it can be concluded that each song in the lyrics has different signs and meanings. These differences have given different interpretations.